Seeking Culturally Safe Developmental Evaluation: Supporting the Shift in Services for Indigenous Children - Natasha Blanchet-Cohen; Pascale Geoffroy; Luz Luz Marina Hoyos (Journal of MultiDisciplinary Evaluation)
Background: Evaluation methods based on western frameworks that disregard Indigenous peoples’ worldviews and are imposed and implemented by outsiders are problematic for Indigenous communities.